2023
DOI: 10.1002/chem.202301328
|View full text |Cite
|
Sign up to set email alerts
|

Structure Formation in an Ionic Liquid Wetting Layer: A Combined STM, IRAS, DFT and MD Study of [C2C1Im][OTf] on Au(111)

Abstract: In a solid catalyst with ionic liquid layer (SCILL), ionic liquid (IL) coatings are used to improve the selectivity of noble metal catalysts. To understand the origins of this selectivity control, we performed model studies by surface science methods in ultrahigh vacuum (UHV). We investigated the growth and thermal stability of ultrathin IL films by infrared reflection absorption spectroscopy (IRAS). We combined these experiments with scanning tunneling microscopy (STM) to obtain information on the orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
25
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 78 publications
(192 reference statements)
6
25
1
Order By: Relevance
“…The calculated IP density is 1.33 IP nm 2 , which is in good agreement with our measurements. In contrast to the previous work by Buḧlmeyer et al, 43 we did measure not only the reported hexagonal structure of [C 2 C 1 Im][OTf] on Au(111) but also oblique structures at temperatures ≤190 K.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…The calculated IP density is 1.33 IP nm 2 , which is in good agreement with our measurements. In contrast to the previous work by Buḧlmeyer et al, 43 we did measure not only the reported hexagonal structure of [C 2 C 1 Im][OTf] on Au(111) but also oblique structures at temperatures ≤190 K.…”
mentioning
confidence: 74%
“…In the previous study by Buḧlmeyer et al, the 2D glass structure was directly imaged for smaller IL islands and they achieved long-range order by increasing the IL film coverage. 43 In contrast to the work by Buḧlmeyer et al, we measured the change from a 2D glass-like structure to a long-range order as we increased the sample temperature while keeping the coverage constant.…”
Section: Synthesis Of 1-ethyl-3-methylimidazolium Trifluoromethanesul...mentioning
confidence: 95%
See 3 more Smart Citations